Hemimasticatory spasm —a peripheral paroxysmal cranial neuropathy?. Issue 3 (March 1983) - Thompson, PD; Carroll, WM
Abstract : The clinical and electrophysiological features of a case of hemimasticatory spasm are presented. The findings are in many respects similar to those described in hemifacial spasm. A peripheral cranial neuropathy as proposed in hemifacial spasm also may be responsible for hemimasticatory spasm.